ANALISA OPTIMASI INTENSITAS TANAM DAN SENSITIVITAS DAERAH IRIGASI RAMBUT KABUPATEN TEGAL - Khoirina, Fitria Nur; Rispiningtati, Rispiningtati; Asmaranto, Runi (Fakultas Teknik, Universitas Brawijaya, 2015)
Abstrak: Daerah Irigasi Rambut terletak di Kabupaten Tegal, Provinsi Jawa Tengah dengan luas areal 7.634 ha untuk mengaliri Kecamatan Warureja dengan luas areal 3.740 ha dan Kecamatan Suradadi dengan luas areal 3.894 ha. Permasalahan yang ada pada daerah irigasi ini adalah terbatasnya debit yang tersedia di Bendung Cipero terutama pada musim tanam III. Dalam penelitian ini ditekankan bagaimana mengoptimalkan debit irigasi dengan melakukan modifikasi pola tata tanam (5 alternatif modifikasi pola tata tanam) dan penentuan luas tanam untuk memperoleh intensitas tanam paling maksimum dengan keuntungan paling besar sehingga bisa didapatkan pola tanam yang terbaik.Hasil dari optimasi didapatkan intensitas tanam paling maksimum sebesar 216,24% dengan keuntungan sebesar Rp 219.754.752.741,74 yang merupakan hasil optimasi alternatif II. Untuk hasil analisa sensitivitas pada saat MT I harga padi sensitif diantara harga 0 - Rp 15.310.000,00; MT II harga padi sensitif diantara harga 0 - Rp 13.862.500,00 dan saat MT III harga palawija sensitif diantara harga 0 – Rp 8.665.000,00. Sementara itu harga tebu saat MT I, MT II, MT III sensitif diantara harga 0 - Rp 26.585.000,00. Luas lahan MT I sensitif diantara 1.239,71 ha - 7634 ha, luas lahan MT II sensitif diantara 4.562,60 ha - 7634 ha dan MT III sensitif diantara 6.500,36 ha - 7634 ha. Kebutuhan air MT I sensitif diantara 0 – 29.539.900,80 m3, saat MT II sensitif diantara 1.388.893,09 m3 - 2.298.703,41 m3 dan MT III sensitif diantara 1.868.910,43 m3 - 2.138.486,18 m3.Kata Kunci: Irigasi, Optimasi, Sensitivitas, Intensitas Tanam Abstract: Rambut Irrigation district located in Tegal Regency, Central Java Province, with total area of 7.634 ha is used to irrigate Warureja sub-district with 3.740 ha and Suradadu sub-district with 3.894 ha. Main problem in this irrigation district is limited discharge that are available in Cipero Weir especially in 3rd crop season. This study emphasize on optimization of available irrigation discharge by conducting crop pattern modification (5 alternatives) and crop-growing range setting in order to obtain the most effective crop pattern based on the highest cropping intensity which lead to highest yield and economic advantage.Optimization result shows that alternative III of crop pattern modification present highest cropping intensity about 216,24 and provide benefit about Rp 219.754.752.741,74. Value Sensitivity Analysis shows that rice value were sensitive in range of 0 - Rp 15.310.000,00 on 1st crop season (MT I); 0 - Rp 13.862.500,00 on 2nd crop season (MT II), while palawija value is sensitive in range of 0 - Rp 8.665.000,00 on 3rd crop season (MT III). While sugarcane value sensitive in range of 0 - Rp 26.585.000,00 on all crop season (MT I, MT II & MT III). For the Area-Range Sensitivity, 1st crop season (MT1) is sensitive in range of 1.239,71 ha – 7634 ha, 2nd crop season(MTII) is sensitive in range of 4.562,60 ha - 7634 ha and 3rd crop season (MT III) are all sensitive in range of 6.500,36 ha - 7634 ha. Water requirement sensitivity analysis shows that 1st crop season (MT I) sensitive for water requirement in range of 0 – 29.539.900,80 m3. 2nd crop season (MT II) in range of 1.388.893,09 m3 - 2.298.703,41 m3 and 3rd crop season (MT III) in range of 1.868.910,43 m3 - 2.138.486,18 m3.Keywords : Irrigation, Optimization, Sensitivity, Crop Intensity